O patrimônio cultural das comunidades quilombolas do Vale do Ribeira: impactos da metodologia de referenciamento de bens culturais - Mathias, Daniel Santos [UNIFESP] (2020)
This research seeks to deepen reflections about the Cultural Heritage by reviewing the networks around inventory of cultural goods of Quilombola Commnunities in Vale do Ribeira, São Paulo, relating historical and anthropological studies on land and social conflicts. Aiming to create collaborative knowledge with local groups and the third sector in the region, this project investigates the importance of cultural meanings for the policy of preserving their heritage. It also addresses the issue about the relationship with the quilombola territorial naming and identifies and potential challenges to the applicability of the referencing methodology.